Economic Factors and Performance Measurement of Regional Governments in Sumatra and Java - Ryan Saputra Alam; Hurian Kamela (Department of Management FEB Unhas, 2021)
One measurement of performance in local government is the regional government performance score (EKPPD). The purpose of this study was to analyze the influence of economic factors with performance scores in local government. This study conducted 119 cities and regencies in Java and Sumatra for 2 years, 2015-2016. The total sample is 238 cities and districts. The reason for this sample was chosen because Java and Sumatra are two large islands in Indonesia and have quite high economic development. The research method used is regression using panel data. The dependent variable used is the performance score from the Regional Government. The independent variable used is economic factors such as the Human Development Index (HDI). Control variables are Poverty Rate and GINI Coefficient. The results of this study explain that HDI and GINI have a positive effect on the performance of local governments. The contribution of this study provides an explanation that the higher the poverty rate inherent with the better quality of life of the community, prove that developments in the City / Regency in the Regional Government have been implemented by the Regional Government following the capacity of the Regional Government.